Kinetic Study of Cumin Essential Oil and of its Major Components - Benrejdal, A.; Dridi, F.; Nabiev, M.; Benyoussef, E.-H. (Asian Journal of Chemistry, 2011)
Cumin (Cuminum cyminum linn.) is an annual plant of the Umbellifereae family. It has been used for a very long time in traditional medicine in the treatment of diarrhoea, dyspepsia and gastric disorder. In present work we have carried out the extraction of the Algerian essential oil of cumin using the hydrodistillation method. This extraction was followed by a kinetic study of the constituents yield of the cumin essential oil following a given time. The essential oil has been analyzed following the capillary gas-chromatography coupled with mass spectrometry. The achieved results allowed to identify the major components of our essential oil and to determine their yield following the extraction duration.